Eigen value approach to generalized thermoelastic interactions in an unbounded body with circular cylindrical cavity without energy dissipation - Chakraborty, Sanjukta (Zielona Góra: Uniwersytet Zielonogórski)
The theory of generalized thermoelasticity in the context of the Green-Naghdi model - II (thermoelasticity without energy dissipation) is studied for an infinite circular cylindrical cavity subjected to two different cases of thermoelastic interactions when the radial stress is zero for (a) maintaining constant temperature and (b) temperature is varying exponentially with time.
Keywords: eigen value approach; generalized thermoelasticity; Laplace transform and vector- matrix differential equation